"Russian World" Concept: Post-Soviet Geopolitical Ideology and the Logic of "Spheres of Influence". Issue 2 (3rd April 2018) - Suslov, Mikhail
ABSTRACT: In contemporary Russia, geopolitical discourses have become more important than political ideology proper, so the "Russian world" concept is rising to the position of an all-embracing ideology, which maintains that Russia is or should be politically and geographically bigger than the Russian Federation. This means that the idea of "spheres of influence" is embedded into the concept. At the same time, the paper argues that the meaning of the "Russian world" has been differently articulated and differently instrumentalized for political purposes during the last 20 years. It would be an oversimplification to believe that "Russian world" has always been a mere synonym for Russia's neo-imperialist pursuits in the post-Soviet arena. Focusing on discontinuities, the paper identifies three ideological iterations of the "Russian world." The first was de-territorialized and de-centered imagery of the "Russian archipelago" in the 1990s. The second represents adjustment of the concept to the idea of the "sovereign democracy" in the 2000s, when the logic of the "sphere of influence" was injected into the "Russian world." Third, in the 2010s, the "Russian world" has been re-territorialized as an irredentist and isolationist project, aligned with the logic of representing Russia as an alternative, non-Western model of modernity. The bottom line of the argument is that in spite of many innovative and potentially progressive connotations, the "Russian world" concept has displayed a marked tendency towards conservative and anti-Western criticism of globalization, which is characteristic of the logic of the spheres of influence.